Prediction of 5 km trail race performance from a shorter distance trail run - Navalta, J. W.; Radzak, K. N.; Montes, J.; Tanner, E. A.; Bodell, N. G.; Manning, J. W. (Biology of Exercise, 2018)
A common strategy for many runners is to predict race time from a shorter time. It is unknown whether these strategies apply to trail races. The purpose was to determine if a 1-mile time trial on the trail could predict performance on a 5km trail run. Twentysix participants reported to the trailhead and completed a 1-mile and a 5km timed trail run one day apart in a counterbalanced order. Elevation at the trailhead was 1,641 m with a rise of 17 m throughout the marked 1-mile course, and 61 m on the 5km course. Data were analyzed using a Pearson product moment correlation coefficient with significance accepted at the p.0.05 level. A significant correlation was observed between 1-mile time and 5km performance (r=0.952, p=0.0001, R2=0.907, SEE = 1.77). The equation to predict 5km time from the mile time trial was: trail 5km time (minutes as a decimal) = 3.996 x trail mile time (minutes as a decimal) . 3.6011. A 1-mile trail run time trial can be used to predict performance for a 5km trail race. Additionally, based on these data, 5km trail running velocity is approximately 12% less than during a 1-mile trail run bout.